2020
DOI: 10.1037/aca0000194
|View full text |Cite
|
Sign up to set email alerts
|

Problem finding and creativity: A meta-analytic review.

Abstract: This study examined the relationship between problem finding (PF) and creativity. A search of published and unpublished studies in English from 1960 to 2015 resulted in 40 studies with a total of 6,649 male and female participants, with ages ranging from childhood to adulthood. Accordingly, this meta-analysis estimated the population correlations between PF and creativity within the 40 studies; it examined whether the correlations varied according to the sample characteristics or other aspects of the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 78 publications
1
65
0
1
Order By: Relevance
“…This is PROBLEM FINDING, DIVERGENT THINKING AND EVALUATIVE SKILLS 5 why almost all models for creative processes include PF as a separate step for creative problem solving (e.g., Isaksen et al, 2000;Merrifield et al, 1962;Parnes, 1967;Wallas, 1926). PF's importance in this regard has also been attested by a recent meta-analytic review on the relationship between PF and creativity (Abdulla et al, 2020), where the results showed that PF and creativity were significantly correlated (r= .22). Although this effect size is considered small, it is similar to the effect size reported by Kim (2008) in another metaanalysis on the relationship between creativity and divergent thinking (DT).…”
Section: ___________________mentioning
confidence: 85%
“…This is PROBLEM FINDING, DIVERGENT THINKING AND EVALUATIVE SKILLS 5 why almost all models for creative processes include PF as a separate step for creative problem solving (e.g., Isaksen et al, 2000;Merrifield et al, 1962;Parnes, 1967;Wallas, 1926). PF's importance in this regard has also been attested by a recent meta-analytic review on the relationship between PF and creativity (Abdulla et al, 2020), where the results showed that PF and creativity were significantly correlated (r= .22). Although this effect size is considered small, it is similar to the effect size reported by Kim (2008) in another metaanalysis on the relationship between creativity and divergent thinking (DT).…”
Section: ___________________mentioning
confidence: 85%
“…While intuitive thinking about creativity sees the creative process as an act of problem solving (Guilford, 1967), an underappreciated aspect of creativity is problem finding (Abdulla et al, 2020;Guilford, 1950;Runco, 1994), in other words a determination of which problems within a given domain are worthy of being addressed to begin with. Sternberg (1988), in talking about the renowned experiments in the history of psychology, argued that "[p]roblem selection was far more important than problem solution in determining the classic role of these experiments" (p. 133).…”
Section: Domain and Time-framementioning
confidence: 99%
“…Yet, scientific thinking depends very heavily on the problem-finding, creative phase of research. Moreover, diverse recent models of problem-solving place substantial emphasis on problem finding ( Abdulla and Cramond 2018 ; Abdulla et al 2018 ; Arlin 1975 ; Arlin 1975–1976 ; Mumford and McIntosh 2017 ; Mumford et al ( 1991 , 2012 ); Simonton 2004 ). Our goal, therefore, was to place greater emphasis on this problem-finding phase in the current research.…”
Section: Theoretical Basismentioning
confidence: 99%